Cassava - Lynam, John K. (International Center for Tropical Agriculture, 1980)
In L.A., food uses determine the demand for cassava, especially in rural areas, because of problems in marketing this highly perishable crop. Production is stagnant due apparently to the lack of growth in demand. A significant growth market for cassava products is needed; e.g., the alcohol program in Brazil. Outside of Brazil, market growth will come in the animal feed sector but to exploit these markets competitively, increasing technology will be required. (CIAT)